2021
DOI: 10.1111/ijcp.14937
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of Tp‐e interval and Tp‐e/QT ratio in patients with hyperthyroidism before and after thyroid surgery

Abstract: Background Ventricular repolarisation is assessed using the Tp‐e interval and QT interval corrected by the heart rate (QTc) via an electrocardiogram (ECG). Prolonged Tp‐e/QTc is related with an increased risk of arrhythmias and cardiac mortality. Objective This study was conducted at a single centre in collaboration with general surgery and cardiology clinics. We aimed to appraise the assessment of Tp‐e interval and Tp‐e/QT ratio in patients with hyperthyroidism before and after thyroid surgery. Methods Totall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In a study by Aydin et al, the comparison of the preoperative and postoperative Tp-e levels of hyperthyroid patients revealed an improvement in the Tp-e levels after surgical treatment. It is worth noting that patients in both groups were euthyroid and received medical treatment [22]. Accordingly, Graves' disease may increase susceptibility to arrhythmia independently of thyroid hormone level as well.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Aydin et al, the comparison of the preoperative and postoperative Tp-e levels of hyperthyroid patients revealed an improvement in the Tp-e levels after surgical treatment. It is worth noting that patients in both groups were euthyroid and received medical treatment [22]. Accordingly, Graves' disease may increase susceptibility to arrhythmia independently of thyroid hormone level as well.…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular repolarization markers such as Tp-e interval, Tp-e/ QT, and Tp-e/QTc ratios have been evaluated in many clinical situations [10][11][12][13][14] . The Tp-e interval may represent the transmural distribution of repolarization, and an increased Tp-e interval is associated with malignant ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…6 Also, Aydin et al showed that the Tp-e interval, as well as the Tp-e/QT and Tp-e/QTc ratios, was shortened in patients with hyperthyroidism after thyroid surgery; QT dispersion was also significantly different before and after thyroid surgery. 7…”
Section: Dear Editormentioning
confidence: 99%
“…6 Also, Aydin et al showed that the Tp-e interval, as well as the Tp-e/QT and Tp-e/QTc ratios, was shortened in patients with hyperthyroidism after thyroid surgery; QT dispersion was also significantly different before and after thyroid surgery. 7 Is there any data about the QT dispersion in the Hepsen et al study? 1 What was the success rate for all surgical procedures?…”
mentioning
confidence: 98%